A method for design of high strength concrete composition considering curing temperature and duration. (20th October 2018) - Dvorkin, L.; Zhitkovsky, V.; Stepasyuk, Y.; Ribakov, Y.
Highlights: HSC mix design considering curing temperature and duration is proposed. A method for predicting HSC strength after steaming and normal hardening is proposed. Good correlation between the calculated and experimental values was obtained. Abstract: The paper deals with experimental results on temperature and curing duration influence on strength properties of high strength concrete (HSC). Dependences for calculating strength of high strength concrete at 12 h, 1, 7 and 28 days are developed for normal hardening conditions. Equations, allowing considering curing temperature in diapason between 5 and 40 °C as well as curing duration are proposed. The influence of steam curing parameters on HSC strength characteristics is investigated. Methodology for predicting concrete strength after steam curing and further normal hardening is proposed. The obtained calculation dependences and experimental-statistical models provide wide possibilities for design of effective high strength concrete compositions.